Effectiveness of Using PLN Mobile Application for Easy Customer Service at PLN Delitua Medan Indonesia - Widuri, Bunga; Widodo, Slamet (Sinergi International Journal of Economics, 2023)
Today's information technology has been widely applied in various fields such as banking, education, economics, health and also electricity. The development of technology, especially information, is currentlyincreasingly rapid, this has led to many companies trying to come up with new innovations in terms of customer service which will certainly make it easier for customers to make transactions or other activities. The development of the internet has an increasingly strong influence on life, this cannot be denied, as evidenced by the increasing number of internet users from year to year. Therefore, in an effort to increasethe reliability of PLN services, PLN has innovated by releasing the PLN Mobile Application. The researchaims to determine the level of understanding of PLN customers and to determine the factors that influenceuser satisfaction of the PLN Mobile application, both from the customer and PLN officer side. The method used in this research is descriptive qualitative with data collection techniques through interviews with PLN customers and PLN officers at PLN ULP Delitua. The results of this research can be used as recommendations regarding system development by paying attention to factors that have a significant influence on customer satisfaction among PLN Mobile application user.